DETERMINAN YANG MEMPENGARUHI PENERAPAN ASUHAN KEPERAWATAN DIGITAL - Arif, Rizca; Asmirajanti, Mira; Riyanto, Agus; Inayah, Iin; Rohayati, Lilis (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Minister of Health Regulation No. 24 of 2022 mandates all healthcare facilities to implement electronic medical records. Digital nursing care at RSAU dr. M Salamun has not yet been optimally implemented due to a lack of knowledge, attitude, motivation, skills, and insufficient management support in the implementation of digital nursing care. This study aims to find out the Determinants that Affect the Implementation of Digital Nursing Care at RSAU dr. M Salamun. The research design used is quantitative research using analytical surveys and Cross Sectional approaches. The population and sample used in this study are all outpatient and inpatient nurses at RSAU dr. M Salamun which totals 160 nurses. The types of data in this study are primary and secondary data, the data collection tool used in this study is a questionnaire. The data analysis techniques used in this study are unvariate analysis, bivariate analysis and bivariate analysis. The study results indicate that knowledge has a significant effect on the implementation of digital nursing care (p-value 0.001), attitude has a significant effect on the determinants of the implementation of digital nursing care (p-value 0.000), while motivation, skills, and management support do not have a significant effect on the determinants of the implementation of digital nursing care. The test results show that collectively or simultaneously, the variables of knowledge, attitude, motivation, skills, and management support significantly influence the determinants of the implementation of digital nursing care. The attitude variable has the most dominant influence on the determinants of the implementation of digital nursing care at RSAU dr. M Salamun, with a p-value of 0.000. Based on these research findings, it is recommended that the hospital establish regulatory commitments and conduct socialization efforts for all nurses regarding the use of digital nursing care to raise awareness and create a positive attitude towards the use of digital nursing care technology that complies with accreditation standards.